Land-use changes lead to functional loss of terrestrial mammals in a Neotropical rainforest - Magioli, Marcelo; Ferraz, Katia Maria Paschoaletto Micchi de Barros; Chiarello, Adriano Garcia; Galetti, Mauro [UNESP]; Setz, Eleonore Zulnara Freire; Paglia, Adriano Pereira; Abrego, Nerea; Ribeiro, Milton Cezar [UNESP]; Ovaskainen, Otso (Elsevier, 2021)
Land-use changes are a main driver of modifications in tropical ecosystems, leading to the loss of species and ecological traits and affecting key ecological functions. Although much attention has been given to predict the effects of species loss on ecological processes, information on the large-scale effects of land-use changes over ecological functions is scarce. Here, we detected erosion in the prevalence of ecological functions performed by mammals in response to land-use changes in the Atlantic Forest of Brazil. By analyzing the loss of different ecological functions (vertebrate and invertebrate predation, seed dispersal, seed depredation, herbivory) performed by mammal assemblages in a deforestation gradient, we observed that vulnerable functions (performed by sensitive species, such as browsing, seed depredation, medium and large vertebrate predation) were positively related to patch size and forest cover and negatively related to anthropogenic cover. These relationships were reversed for persistent functions (performed by resilient species, such as grazing, small seed dispersal, small vertebrate and invertebrate predation). Vulnerable functions were virtually restricted to large forest remnants, while persistent functions were prevalent in human-modified landscapes. Disturbed forests are not necessarily empty of mammal species, but there is a substantial loss of ecological functions across most of the Atlantic Forest. Five out of ten ecological functions lose prevalence in small forest remnants. Nonetheless, these small remnants serve as refuges for the remaining biodiversity and are on the verge of the functional extinction of important processes. The erosion of ecological functions provided by mammals compromise the persistence of Atlantic Forest's biodiversity.
Keywords: Atlantic Forest; Diet; Ecological functions; Forest fragmentation; Habitat loss; Hierarchical modeling; Human-modified landscapes